Pelatihan Desain dengan Software CATIA untuk Mengembangkan Kompetensi Teknologi bagi Santri Al Muthi’in Yogyakarta - Hartini, Dwi; Junaidin, Buyung; Santoso, Djarot Wahju; Prattiwi, Elisabeth Anna (Mestaka: Jurnal Pengabdian Kepada Masyarakat, 2026)
The rapid development of digital technology has brought significant changes to both education and industry. One of the technological competencies highly required in modern industries is Computer Aided Design (CAD), which enables product design processes to be carried out efficiently and with high precision. Computer Aided Three-dimensional Interactive Application (CATIA) is a CAD software widely used in various industrial sectors, including manufacturing, automotive, and aerospace. However, opportunities to learn industry-level design software are still limited for many santri. This community service activity aims to enhance technological literacy and basic design skills through CATIA software training for santri of Al Muthi’in. The training was conducted using a hands-on learning approach at the Institut Teknologi Dirgantara Adisutjipto. The training materials covered the introduction to basic CAD concepts, CATIA interface recognition, two-dimensional sketch creation, and simple three-dimensional modeling. The results of the activity indicate an improvement in the santri’s understanding of CAD concepts and their ability to independently create basic three-dimensional designs. This activity is expected to serve as an initial step in strengthening the technological competencies of santri.